2010
DOI: 10.1109/tns.2010.2059043
|View full text |Cite
|
Sign up to set email alerts
|

High Radiation Sensitivity of Chiral Long Period Gratings

Abstract: The radiation sensitivity of chiral long period gratings was investigated for the first time. After a Co-60 gamma dose of 100 kGy they show radiation-induced changes of their transmission dip wavelength of up to 10 nm, which is 100 to 1000 times higher than the radiation-induced wavelength shift of different fiber Bragg grating types. They can therefore be used as radiation sensors down to doses of 10 Gy or even below, but not for accurate dose measurements since the size of the wavelength shift after a certai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 27 publications
2
27
0
Order By: Relevance
“…We have used Gamma radiation exposure and slight tapering of fiber with CO 2 laser as the tools for tuning near TAP LPG. Wavelength shift of ±35nm was observed for gamma radiation exposure of 6kGy which is higher than the wavelength shift reported in [8]. Simulation of PMC for increased and decreased value of core refractive index showed that the gamma radiation exposure is effectively increasing the core refractive index by an order of 10 -5 -10 -4 , which is significant for a near TAP-LPG.…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…We have used Gamma radiation exposure and slight tapering of fiber with CO 2 laser as the tools for tuning near TAP LPG. Wavelength shift of ±35nm was observed for gamma radiation exposure of 6kGy which is higher than the wavelength shift reported in [8]. Simulation of PMC for increased and decreased value of core refractive index showed that the gamma radiation exposure is effectively increasing the core refractive index by an order of 10 -5 -10 -4 , which is significant for a near TAP-LPG.…”
Section: Discussionmentioning
confidence: 58%
“…It has been reported that certain Fiber Bragg gratings (FBGs) can be used for radiation dose sensing [7]. Chiral LPG has shown 10 nm shift for 100 kGy dose of gamma radiation [8]. Cladding etching has been earlier used for resonance peak positioning in LPG [9].…”
Section: Introductionmentioning
confidence: 99%
“…2,3,5) and of the most sensitive ones (nos. 4,6,7,8) differed by more a factor of 100. Fibers that show higher attenuation at 1550 nm also show higher RIA down to UV wavelengths.…”
Section: Radiation Sensitivity Of Chiral Fiber Long Period Gratingsmentioning
confidence: 97%
“…An overview of manufacturers, dimensions, and core and cladding dopant concentrations in these fibers is given in Table I 7 . The core of the Nufern 1 fiber is highly doped with P, whereas the cores of the Nufern fibers 2 and 3 are doped with rare earth elements.…”
Section: Manufacturing Chiral Fiber Gratings For Radiation Sensingmentioning
confidence: 99%
See 1 more Smart Citation